PP29 Number of lifestyle risk factors is associated with increased risk of hospital admission among community-dwelling older people: the hertfordshire cohort study. (31st August 2015) - Westbury, LD; Syddall, HE; Simmonds, SJ; Robinson, SM; Cooper, C; Sayer, AA
Abstract : Background: Previous studies have shown a relationship between increased number of lifestyle risk factors and adverse health outcomes such as mortality and low physical function. We hypothesised that the number of lifestyle risk factors (out of low physical activity, poor diet, obesity and smoking) may be associated with subsequent hospital admission among community-dwelling older people. Methods: From 1998–2004, 2997 community-dwelling men and women (aged 59–73) who participated in the Hertfordshire Cohort Study (HCS) completed a baseline assessment. Physical activity was assessed using a questionnaire with a score ranging from 0–100; diet was assessed using a food frequency questionnaire and a prudent diet score, to indicate compliance with a healthy dietary pattern, was derived using principal component analysis. Smokers were regarded as individuals who were current smokers; obesity was defined as a BMI of 30.0 kg/m 2 or more; poor diet was defined as having a prudent diet score in the bottom quarter of the distribution and low physical activity was defined as having a physical activity score of 50 or less. Hospital Episode Statistics and mortality data up to 31/03/10 were linked with the HCS database. Survival analysis models and Poisson regression models were used to examine the association between the number of risk factors and the risk of the following types of hospital admission: any, elective, emergency, long stay (>7 days) and readmission within 30 days. Results: There was a graded increase in the risk of all types of admission among men and women as the number of risk factors increased. For example, the unadjusted hazard ratios for emergency admission among men were: one risk factor vs none 1.11[95% CI: 0.96, 1.29], two vs none 1.25[95% CI: 1.04, 1.49], three or four vs none 1.74[95% CI: 1.40, 2.15]; and among women were: one vs none 1.15[95% CI: 0.96, 1.38], two vs none 1.44[95% CI: 1.17, 1.76], three or four vs none 1.96[95% CI: 1.36, 2.81]. Associations for all types of admission remained significant after adjustment for age and number of systems medicated. Although, as in many cohort studies, a healthy participant effect is apparent in HCS, this is unlikely to have affected these results since this analysis was internal. Conclusion: This study provides the first evidence that the number of lifestyle risk factors among community-dwelling men and women is associated with risk of subsequent hospital admission. As lifestyle risk factors often coexist and are more prevalent among lower socioeconomic groups, encouraging healthy lifestyles may have the potential to avert admission and reduce inequalities in health.